Septal glucagon-like peptide 1 receptor expression determines suppression of cocaine-induced behavior - Harasta, Anne E.; Schneider, Miriam (Neuropsychopharmacology, 2015)
Glucagon-like peptide 1 (GLP-1) and its receptor GLP-1R are a key component of the satiety signaling system, and long-acting GLP-1 analogs have been approved for the treatment of type-2 diabetes mellitus. Previous reports demonstrate that GLP-1 regulates glucose homeostasis alongside the rewarding effects of food. Both palatable food and illicit drugs activate brain reward circuitries, and pharmacological studies suggest that central nervous system GLP-1 signaling holds potential for the treatment of addiction. However, the role of endogenous GLP-1 in the attenuation of reward-oriented behavior, and the essential domains of the mesolimbic system mediating these beneficial effects, are largely unknown. We hypothesized that the central regions of highest Glp-1r gene activity are essential in mediating responses to drugs of abuse. Here, we show that Glp-1r-deficient (Glp-1r−/−) mice have greatly augmented cocaine-induced locomotor responses and enhanced conditional place preference compared with wild-type (Glp-1r+/+) controls. Employing mRNA in situ hybridization we located peak Glp-1r mRNA expression in GABAergic neurons of the dorsal lateral septum, an anatomical site with a crucial function in reward perception. Whole-cell patch-clamp recordings of dorsal lateral septum neurons revealed that genetic Glp-1r ablation leads to increased excitability of these cells. Viral vector-mediated Glp-1r gene delivery to the dorsal lateral septum of Glp-1r−/− animals reduced cocaine-induced locomotion and conditional place preference to wild-type levels. This site-specific genetic complementation did not affect the anxiogenic phenotype observed in Glp-1r−/− controls. These data reveal a novel role of GLP-1R in dorsal lateral septum function driving behavioral responses to cocaine.
Gesehen am 25.01.2018